A Latent Transition Analysis of Self-Reported Reasons for Marijuana Use During Young Adulthood. Issue 1 (March 2021) - Bray, Bethany C.; Berglund, Patricia A.; Evans-Polce, Rebecca J.; Patrick, Megan E.
Individuals' reasons for marijuana use have been linked to their risk for continued use and development of disordered use. Although individuals tend to have multiple reasons for use, co-occurrence of reasons is not always accounted for in analytic approaches. Latent transition analysis (LTA) is ideal for modeling transitions in co-occurring reasons. Using longitudinal panel data from Monitoring the Future, LTA was used to identify profiles of self-reported reasons for marijuana use among young adults, examine transitions between profiles, and determine whether cohort, gender, race/ethnicity, parent education, grade of first marijuana use, and 4-year college attendance predicted transitions between profiles. Data included senior year cohorts from 1976–2009 and were collected at ages 19/20, 21/22, and 23/24 (weighted n = 7, 294; 55.9% female; 79.3% White). Five latent classes were identified: Non-Users and individuals with Experimental, Typical, Get High + Relax, and Escape + Coping Reasons. Transitions among Non-Users, Experimental Reasons, and Typical Reasons were common; generally, those with earlier cohort membership, early initiation, college non-attending parents, and college attendance were more likely to make transitions to higher-risk classes. As the legalization of recreational marijuana use continues to expand, change over time in reasons for use should be considered carefully as interventions are developed and implemented.